Diving into the World of Sound and Light, Understanding Their Properties, Propagation and Uses - Anggelia, Shilvy; Rahmawati, Rahmawati; Setiawati, Adinda; Kurniawati, Wahyu (Sean Institute, 2024)
The aim of this research is to introduce students to the basic concepts of sound and light during science learning. This abstract discusses the properties of sound, such as its source, propagation, and how the human ear receives sound. Apart from that, this abstract also discusses light as an energy source that allows us to see objects around us, including how the eye propagates and receives light. Once students understand these concepts, it is hoped that they will be able to understand between sound and light.Sound waves can modulate the amplitude and phase of light, bending it, focusing it, or shifting its frequency. Light can create visible acoustic images or provide detailed information about thermal vibrations in solids and liquids. Diffraction of light waves by sound waves takes several different forms, depending on the two wavelengths and the dimensions of the interaction region. Sound waves can modulate the amplitude and phase of light, bending it, focusing it, or shifting its frequency. Light can create visible acoustic images or provide detailed information about thermal vibrations in solids and liquids. Diffraction of light waves by sound waves has several different forms, depending on the two wavelengths and the dimensions of the interaction area. Sound is a wave produced by a vibrating object. Meanwhile, light is energy that has electromagnetic waves and can propagate in a vacuum. Sound can travel through solids, liquids and gases.